Customer satisfaction towards employees provident fund (EPF) Johor Bahru members services counter / Mustafah Hasim - Hasim, Mustafah (2001)
The Employee provident Fund (EPF) is a fund institution As such, the services and benefits that are obtainable by member take from the services provided by the EPF and also take the form of Withdrawals from a balance he has accumulated over the years with the Fund. As We all know, because the provident fund is a mechanism for compulsory savings, means that every worker especially in private sector are eligible to become EPF member. Hence, it built up a large growing pool of members every year Because of this compulsory saving, EPF members are very sensitive towards services provided by EPF. EPF members feel that they have their rights to do because their future also depends on their savings with EPF. With a large number Of workers registered with the EPF as their members which 10 million, it is Obvious to See receive a complaint on their services including a complaint on EPF counter services. Therefore, this research will undertake a close examination of the EPE members' level of satisfaction towards EPF Johor Bahru member set-vices counter. This research has discovered Very good insight Of the Of satisfaction among the EPF members especially in Johor The researcher identified.